Work Stress in Nurses in Adult Inpatient Wards - Saribu, Hotmaria Julia Dolok; Liestyaningrum, Wiwiek; Suridwan, Wawan (GLOBAL HEALTH SCIENCE GROUP, 2024)
Work Stress is a common phenomenon experienced by nurses, especially those working in adult inpatient wards. High workload, physical and emotional demands, and dynamic work environment can affect nurses' well-being and the quality of services provided. Therefore, understanding the level of nurses' Work Stress is very important to find effective solutions in managing stress in the hospital environment. Objective to describe the level of Work Stress experienced by nurses in the adult inpatient ward of Dabo Regional Hospital and to identify the classification of Work Stress they experience. This study used a descriptive design with a total sampling of 45 nurses in the adult inpatient ward of Dabo Regional Hospital. Data collection was carried out using the Nursing Stress Scale (NSS) questionnaire, which consists of 33 items with a Likert scale. Data were analyzed descriptively to describe the frequency distribution of nurses' Work Stress. The results showed that 53.33% of nurses experienced mild Work Stress, 11.11% of nurses experienced moderate Work Stress, and 35.56% of nurses experienced severe Work Stress. Factors such as coworker support and good management play a role in reducing stress, while high workload and lack of resources contribute to severe stress. Work Stress in nurses in the adult inpatient ward of Dabo Regional Hospital varies, with the majority experiencing mild stress, but a significant number of nurses experiencing severe stress.